The Peran Jaringan Advokasi Transnasional dalam Mendukung Gerakan Anti-Fracking di Inggris 2013-2019 - Amelinda Fairuz Azura; Anggraeni, Silvia Dian (Department of International Relations Universitas Pertamina, 2021)
The implementation of fracking activities in the United Kingdom that involves the pumping of water, chemicals, and sand underground to explore shale gas has caused several hazardous impacts. This situation has sparked protests from various kinds of demonstrators, both individuals and organizations. In response to the public objection to fracking activities, the British Government tended to fight back against the action. The detention of demonstrators ultimately created a pattern of limited advocacy among the public against the British Government. It has prompted an NGO called Friends of the Earth to start mobilizing these issues to the international realm by promoting principled ideas or norms to form a transnational network, aiming to influence national policy. The authors explain the transnational advocacy network's role in influencing British policy by applying the concept of Transnational Advocacy Network (TAN) from Margaret E. Keck and Kathryn Sikkink. Specifically, the role is analysed based on TAN’s strategies, namely Information Politics, Symbolic Politics, Leverage Politics, and Accountability Politics. The authors also use Constructivism Theory to explain how norms and ideas can influence national policy. This research uses qualitative methods with secondary data collection techniques to describe and interpret some relevant phenomena to become an integrated explanation.